Synergy between the Rule of Law and Pancasila Democracy in Guaranteeing Human Rights (HAM) - Muhammad Salman Marzuq; Anshori (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2025)
This journal analyzes the crucial interconnection between the concepts of the rule of law, democracy, and the guarantor of human rights (HAM). In the modern context, these three pillars are seen as fundamental prerequisites for the realization of a just, stable, and prosperous society. The rule of law provides the basis for legality and legal certainty, democracy ensures people's participation and accountability of power, while human rights are the essence and ultimate goal of state administration. This journal will describe how the elements of the rule of law and democracy strengthen each other to create an environment conducive to the protection, advancement, enforcement, and fulfillment of human rights.